The Evolution of Tariqah in Sufism - Falquinzani, Alzena Mahesadewi; Rahma, Bella Putri; Amin, Maulida Izzatul (Proceedings of International Conference on Muslim Society and Thought, 2024)
In the modern world, tariqah is something that is very much needed by Muslims. Because with tarekat, humans have means and ways to return and recognize the nature of God in depth. In the history of its development, Tarekat not only focuses on Sufism or the teachings of its teachers (Mursyid), but also follows political activities. For example, the Tijaniyah Order is known as a political movement that opposed French colonization in North Africa. This research uses a qualitative method with a historical approach that refers to books, journals, with the concept of library research. The purpose of this tarekat in general is to strengthen the faith of a servant to his Lord. The results show that a tariqah can expand in various parts of Islam in large numbers. Tariqah in Sufism have developed widely. Some of which are such as Qadiriyah, Naqsyabandiyah, and Shadziliyah and others.